Effects of behavioural family therapy intervention on juvenile delinquents at Ahvaz Correction Centre in Iran - Baratvand, Mahmood (2011)
Delinquency as a social dilemma exists in all societies. The phenomenon imposes costs on all levels of society, especially the family institution. This problem is being experienced acutely in the city of Ahvaz in Iran. Behavioural family therapy has been successfully used to solve the problem. A mixed method of sampling, proportional allocation and matched pairs, was applied. Accordingly, initially, the sample with respect to the population of each criminal subgroup was determined. Subsequently the subjects were matched with respect to the variables of age, socioeconomic status and type of crime. These matched subjects, were then assigned to the experimental and control groups randomly. The sample consisted of 124 adolescents between ages 13-17 who were sentenced to stay at Ahvaz Correction Centre by the court. There were two main groups, the treatment and the comparison group with three subgroups of thieving (24), physical aggression (20) and sexual crimes (18) in each of the subgroups. The n =124 meets the requirements of reducing Type II error determined by α =.05, u = 1, power at .80 and medium effect size f =.26. The treatment was conducted in 7 sessions of group-based behavioural family therapy, lasting 90 minutes each session and administered during the 3 months for the duration of the research. The intervention, Behavioural Family Therapy, was based on social learning and reinforcement theories. The instruments consisted of the questionnaires of delinquent’s assessment by parents (Q-DAP-2009), the Socio-Economic Status Questionnaire of Monitoring after Release (SES-Q-MAR-2000), and also extracted data obtained from the judiciary system. The data were analysed using repeated measures ANOVA and matched pairs t-test. The findings indicated that there were differences between the experimental and control groups on all the hypotheses with regard to the studied variables in this study, including behaviour correction, relationship with siblings, peers and parents, social and school adaptation, academic behaviour, drug abuse tendency, sexual behaviour and recidivism rate. However, no significant change was observed between the criminal subgroups of the experimental group except in the case of recidivism. The sub group on physical aggression did not show significant difference in the recidivism rate during three months after releasing compared to the control group. Thus, it can be concluded that all subjects in the experimental group benefitted from the treatment regardless of the crimes which they committed. These results provided some evidences which supported the premise that by applying behavioural family therapy for delinquent behaviours, may lead to a decrease in delinquent behaviours of the group. This study, howeve investigated. Nevertheless, the findings suggested that involving families in the process of rehabilitation may provide an encouraging result in moderating the behaviours of delinquents